Analisis Daya Tarik Bangunan Menara Kudus sehingga Dikunjungi Wisatawan dan Pengaruhnya terhadap Pendapatan Para Pedagang - Muhadirin Muhadirin (AL-BURHAN, 2022)
Central Java province has many relics of very large religious tourism objects, one of which is in the Kudus Regency, namely the Kudus Tower. Menara Kudus is one of the most monumental buildings from the legacy of Sunan Kudus. Menara Kudus has an attraction so that it is never empty of tourist visits from various regions. After visiting the tower, tourists buy souvenirs and small snacks typical of the sanctuary as gifts for the family. This study aims to determine the level of satisfaction of tourists to the holy tower and to determine the amount of income of the traders. Methods This research uses a qualitative approach with the type of field research, the research is carried out in the holy tower.Data was collected through observation, direct interviews, then recording dialogues, and documentation. In this study, the research data was carried out by means of triangulation. The analysis process is carried out simultaneously with data collection through several stages, namely data reduction, data presentation, and conclusions. The results showed that: First; the traders who sell are mostly not local people. Second; merchants understand the busy time of tourist visits to the holy tower. The size of the income from traders can be caused by many or few tourist visits and ownership status. The conclusion shows that traders who stay at the same time as residents in the village get increased income. Meanwhile, traders with the ownership status of renting a place for weekdays experience a decrease in income, but during busy times, they can get an increase in income